1995
DOI: 10.1016/0735-1097(94)00446-w
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic indexes of dispersion of ventricular repolarization: An isolated heart validation study

Abstract: The JT and QT dispersion correlate significantly with dispersion of APD90 and recovery time. The ECG assessment of dispersion of repolarization can be improved by three new ECG dispersion indexes: T peak to T end interval, total T wave area and late T wave area. These new indexes should be tested clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
183
2
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(195 citation statements)
references
References 24 publications
4
183
2
6
Order By: Relevance
“…Various Although the TTC generally has a good prognosis and ventricular arrhythmias are quite rare (5), the severe prolongation of the QT interval is to be considered as a predictor for the risk of sudden death (8). Sudden death is also a complication of AN, particularly if complicated by cardiac involvement (12).…”
Section: The Pathogenesis Of the Ttc Is Not Clear But Multivessel Epimentioning
confidence: 99%
“…Various Although the TTC generally has a good prognosis and ventricular arrhythmias are quite rare (5), the severe prolongation of the QT interval is to be considered as a predictor for the risk of sudden death (8). Sudden death is also a complication of AN, particularly if complicated by cardiac involvement (12).…”
Section: The Pathogenesis Of the Ttc Is Not Clear But Multivessel Epimentioning
confidence: 99%
“…33 Other noninvasive measures of repolarization abnormalities such as QT dispersion, QT dynamicity and T-wave alternans could also be used to assess overall vulnerability to arrhythmias. 34,35 …”
Section: Determining Arrhythmic Riskmentioning
confidence: 99%
“…Variability of the QT interval provides a measure of pro-arrhythmic electrical instability [18,19] . The QT interval was the time from the initial deflection from the isoelectric PR segment to the point at which voltage returned to the isoelectric TP segment.…”
Section: Qtc Interval Variabilitymentioning
confidence: 99%
“…Pyruvate stabilizes cardiac electrical function: role of ATP: ADP ratio Victims of hemorrhage are at risk of developing cardiac electrical instability [47] which can be monitored by assessing QTc variability [18,[48][49][50] . ROS have been implicated in the pathogenesis of arrhythmias, and it has been suggested that the antioxidative properties of certain medications could suppress ROS-mediated arrhythmogenesis [40] .…”
mentioning
confidence: 99%